The individual and combined impact of environmental taxes in Chile − A flexible computable general equilibrium analysis. (1st January 2023) - Mardones, Cristian; Ortega, José
Abstract: Many studies simulate carbon taxes with computable general equilibrium (CGE) models, but there is scarce evidence about how other environmental taxes implemented simultaneously reinforce or lessen the impacts. This study aims to determine the individual and combined effect of taxes on CO2 and other local air pollutants (SO2, NOX, and PM) currently applied in Chile. A flexible CGE model is used to sensitize the results, allowing two nested production structures to be compared. Both nested production structures include a high disaggregation of the energy sector that considers different fossil fuels and renewable energies. The results show that environmental taxes reduce between 5.4% and 6.9% of net CO2 equivalent emissions in the most realistic scenarios. In addition, the carbon tax explains 84%–85% of the drop in net CO2 equivalent emissions, 81%–82% of the reduction in fossil energy consumption, 76%–78% of the decline in GDP, and generates co-benefits by reducing local air pollutants. The tax on PM emissions is the second more relevant to reduce net CO2 equivalent emissions, while taxes on SO2 and NOX emissions have marginal effects. By comparing the impacts of both structures to previous studies based on microdata, it is concluded that the KL-EM provides the best results. Highlights: A flexible CGE model is used to simulate environmental taxes on global and local air pollutants. The two most popular nested production structures are compared. KL-EM provides the more realistic results to simulate environmental taxes. Chilean environmental taxes reduce between 5.4% and 6.9% of net CO2eq emissions. The carbon tax explains around 70% or 80% of the impacts on the economy and emissions.